The Effect of a Combination of Vibration and External Cold on Pain Caused during Vaccine Injection in Infants: A Randomized Clinical Trial - Zahra Unesi; Zahra Amouzeshi; Javad Jamavar; Fatemeh Mahmoudzadeh Zarandi (International Journal of Clinical Practice)
Aim. This study was conducted to determine the effect of combining vibration and external cold on pain caused by vaccine injection among six-month-old infants. Design. Randomized controlled trial. Methods. In this clinical trial, 80 eligible infants were selected from the infants referred to a health center as per the inclusion criteria. The infants were assigned to either a control group or an intervention group by block randomization. In the intervention group, a vibrating and cold device was placed above the injection site from one minute before to 15 seconds after the pentavalent vaccine injection. In the control group, no intervention was performed, and they were vaccinated according to the routine procedure. The pain status in the two groups was measured using the Modified Behavioral Pain Scale (MBPS) 15 seconds after the injection, and the crying duration was assessed from the injection of the vaccine till the end of it. Data were analyzed in SPSS 23 software using Mann–Whitney, t, Spearman, and chi-square tests. The level of significance was set to p<0.05. Results. Most participants in the control (55%) and intervention (55%) groups were girls. Statistical data analysis of 80 infants showed that the mean pain intensity (p=0.032) and duration of crying (p=0.0001) in the intervention group (6.1 ± 1.8, 32.47 ± 16.78) were lower than those of the control group (7.2 ± 0.1, 51.02 ± 25.9), respectively. Conclusion. Because the intensity of pain, especially the duration of crying, was lower in the intervention group than in the control group, we may suggest that nurses use simple pain relief solutions in vaccination centers, such as a combination of vibration and cold. This trial is registered with IRCT201207157130N2.